Fighting for abortion rights: Strategies aimed at managing stigma in a group of Italian pro-choice activists. (February 2023) - Giovannelli, Ilaria; Mannarini, Terri; Spaccatini, Federica; Pacilli, Maria Giuseppina
Despite societal changes in Western countries, abortion continues to be morally stigmatized. While research on abortion stigma targeted both at people who seek or voluntarily terminate their pregnancy and abortion providers has been conducted, stigma directed at those who advocate abortion rights has remained under-researched. The purpose of this study was to deepen understandings of abortion stigma in relation to Italian cisgender female pro-choice activists. Accordingly, a qualitative study was conducted to examine how participants experienced, perceived, and internalized stigma, as well as the strategies they employed to manage it. The sample included 34 Italian cisgender female pro-choice activists who were actively engaged in movements at the time of the study, including organizations or unions that publicly defend the right to abort. The findings revealed that participants perceive they are targets of negative stereotyping and behaviors. Nevertheless, they do not internalize the stigma and use different strategies to manage it, such as speaking openly about their activism.